2009
DOI: 10.1159/000260041
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Volume and Albuminuria as Markers of Birth Weight-Blood Pressure Relationship in Essential Hypertension

Abstract: Our aim was to analyze whether birth weight contributes to future hypertension through reduced kidney volume, and whether albuminuria could be a marker of this pathway. We included 103 patients with newly diagnosed essential hypertension and 92 normotensive controls. Blood pressure (BP) was measured using a mercury sphygmomanometer and a ABP monitor. Kidney volume was determined by ultrasound. Data on birth weight were obtained from mothers. Albuminuria was determined in 24-hour urine samples. Hypertensive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…A total of 51 (Tables ) relevant papers finally met the inclusion and exclusion. Of them, 36 followed a cohort design, 9 a case–control design and 5 were of cross‐sectional design, while 1 was a randomized control trial . Most of them collected birth weight retrospectively by chart review with only four studies collecting birth weight prospectively from birth records.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 51 (Tables ) relevant papers finally met the inclusion and exclusion. Of them, 36 followed a cohort design, 9 a case–control design and 5 were of cross‐sectional design, while 1 was a randomized control trial . Most of them collected birth weight retrospectively by chart review with only four studies collecting birth weight prospectively from birth records.…”
Section: Resultsmentioning
confidence: 99%
“…One recorded self-reported 30 birth weight, and three did not mention their methodology. 43,54,60 Eight studies included patients attending hospitals or clinics where they were enrolled, 37,45,56,61,66,67,71,74 while the remainder were community based. One community-based study was conducted among kidney donors.…”
Section: Overall Characteristicsmentioning
confidence: 99%
“…31 The Uppsala Family Study reported by Nitsch et al examined Swedish pairs of consecutive healthy full siblings to identify determinants of kidney function as measured by levels of cystatin C. 117 Lower maternal education attainment was associated with a higher level of cystatin C, and after adjusting for gestational age, maternal parity, sex, and age of the child, there was a nonsignificant decrease in cystatin C levels as birth weight increased. Associations between higher blood pressure and albumin excretion and lower birth weight have been reported from Brazil 118 and Croatia 119 and for microalbuminuria in children born during the Dutch famine in World War II. 120 …”
Section: Evidence From Other Countriesmentioning
confidence: 96%
“…Bakker and colleagues did not detect an association between renal volume and BP in their cohort study of 6397 children. Similarly, Laganović and colleagues showed that the relationship between BP and birth weight was not mediated by renal volume among their patients.…”
Section: Discussionmentioning
confidence: 90%